Wetland wastewater treatment systems : a New Zealand based review : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology at Massey University - Shilton, Andrew Nicholas (Massey University, 1990)
Natural and constructed wetlands have proven capable of providing a high standard of renovation to wastewater and their use as engineered treatment systems is rapidly developing in New Zealand and overseas. This thesis begins by examining the nature or the wetland environment and outlines the renovating processes it contains. The different types of wetland treatment systems are reviewed. Discussion continues into design and management principles which include physical and process design and hydrological and biotic considerations. Finally a review is made of the application of wetlands to the treatment of domestic sewage, non-point pollution, and industrial wastewaters. The conclusion is reached that wetland treatment systems offers an innovative and appropriate solution to a wide range of New Zealand's waste treatment problems and are likely to become an increasingly common treatment option in this country.
Keywords: New Zealand; Constructed wetlands; Land treatment of wastewater